Plan de negocio para la creación de una empresa de gestión de eventos - Desiderio Troya, María Fernanda (2023)
The issue related to the creation of an events company for homes, industry and companies in the Durán canton and its surroundings require collective interest and that you provide all the decorative, environmental and technological conditions. The objective is to analyze the operational and financial viability in the creation of the events room, for which a mixed approach methodology is applied where the exploratory, non-experimental and descriptive method is used with instruments such as observation, interviews and point the results achieved for the economically active population analyzed suggest the attachment of information continuous through the digital means of communication, in addition to all the additional services offered to guarantee the success of a training, onomastics or any other type of event, in conclusion, a financial operational feasibility is obtained by maintaining as a result a sustainable return of the investment and a positive net present value giving the sustained feasibility within the business plan carried out.